Targeting of HIF-alpha to the von Hippel-Lindau ubiquitylation complex by O2-regulated prolyl hydroxylation. - Jaakkola, P; Mole, D; Tian, Y; Wilson, M; Gielbert, J; Gaskell, S; von Kriegsheim, A; Hebestreit, H; Mukherji, M; Schofield, C; Maxwell, P; Pugh, C; et al. (2001)
Hypoxia-inducible factor (HIF) is a transcriptional complex that plays a central role in the regulation of gene expression by oxygen. In oxygenated and iron replete cells, HIF-alpha subunits are rapidly destroyed by a mechanism that involves ubiquitylation by the von Hippel-Lindau tumor suppressor (pVHL) E3 ligase complex. This process is suppressed by hypoxia and iron chelation, allowing transcriptional activation. Here we show that the interaction between human pVHL and a specific domain of the HIF-1alpha subunit is regulated through hydroxylation of a proline residue (HIF-1alpha P564) by an enzyme we have termed HIF-alpha prolyl-hydroxylase (HIF-PH). An absolute requirement for dioxygen as a cosubstrate and iron as cofactor suggests that HIF-PH functions directly as a cellular oxygen sensor.